Deposition Kinetics and Thermal Properties of Atmospheric Plasma Deposited Methacrylate‐Like Films. Issue 5 (29th September 2015) - Scheltjens, Gill; Da Ponte, Gabriella; Paulussen, Sabine; De Graeve, Iris; Terryn, Herman; Reniers, François; Van Assche, Guy; Van Mele, Bruno
Abstract : Allyl methacrylate (AMA), methyl methacrylate (MMA), and propyl isobutyrate (PiB) are plasma deposited at ambient temperature in an atmospheric DBD reactor to assess the effect of precursor carbon double bond unsaturations. The specific plasma deposition rate ( k 0 ) as a function of the Yasuda factor ( Y f ) is quantified empirically by: k 0 = b (1 − exp(– a Yf / b )). Fourier transform infrared analysis indicates a loss of carbonyl functionalities with increasing plasma power, and Raman microscopy shows CC double bonds in all plasma films. The methacrylate‐like plasma films are found to be heterogeneous with a volatile and a cross‐linked fraction observed by thermogravimetric analysis. Differential scanning calorimetry reveals a low glass transition temperature and a characteristic residual reactivity of the coatings. Abstract : The effect of precursor carbon double bond unsaturations on the specific plasma deposition rate ( k 0 ) and thermal properties of plasma deposited methacrylate‐like films is assessed in this work. A significant increase in the plasma deposition rate with increasing number of precursor CC bonds is found. In general, two distinctive thermal characteristics are observed by DSC: a relatively low T g and a residual reactivity in the first heating of the DSC experiment.